Cost-benefits of a domestic abuse program for Australian offenders. Issue 1 (13th March 2017) - Blatch, Chris; Webber, Andrew; O'Sullivan, Kevin; van Doorn, Gerard
Abstract : Purpose: The purpose of this paper is to determine recidivism costs and benefits for 1, 030 community-based male offenders enrolled in a domestic abuse program (DAP) compared to an untreated control group ( n =1, 030) matched on risk factors. Design/methodology/approach: The study time frame was October 1, 2007-June 30, 2010 with reconvictions measured to December 31, 2010. Follow up averaged 19 months. Controls received standard community supervision, but no domestic violence group interventions. Follow up measures included court costs for violent and non-violent reconvictions; re-incarcerations and community-based orders costs measured in days. Findings: Adjusting for time at risk, DAP enrollees had 29 percent fewer reconvictions, 46 percent fewer violent reconvictions, 34 percent fewer custodial days, but 23 percent more days on community orders. Costs: DAP enrollment avoided 2.52 M in custodial costs, but higher community correction costs (+773 K) and court costs (+5.8 K), reducing the DAP's criminal justice system cost savings to 1.754 M (8.92 M for the DAP group compared to 10.67M for controls). Cost benefits: when the 64 DAP program costs were deducted (602 K), the net benefit to the New South Wales criminal justice system was 1, 141 M, or 1, 108 per enrollee, providing a net benefit/cost ratio of 2.89. If the DAP was completed, the net benefit was 1, 820 per offender. These results compares favorably to economic evaluations of other community-based interventions. Practical implications: Group interventions for domestically violent (DV) offenders can provide good investment returns to tax payers and government by reducing demand on scarce criminal justice system resources. The study provides insights into justice costs for DV offenders; a methodological template to determine cost benefits for offender programs and a contribution to cost-effective evidence-based crime reduction interventions. Originality/value: Using a rigorous methodology, official court, custodial and community correction services costing data, this is the first Australian cost benefit analysis of a domestic violence group intervention, and the first to justify program expenditure by demonstrating substantial savings to the criminal justice system.